2020
DOI: 10.5603/pjnns.a2020.0008
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibodies — a revolutionary therapy in multiple sclerosis

Abstract: Introduction.Multiple sclerosis (MS) has an increasing incidence and affects a young segment of the population, having a major impact on patients and consequently on society. The multifactorial aetiology and pathogenesis of this disease are incompletely known at present, but autoimmune aggression has a documented mechanism.State of the art. Since the 1990s, immunomodulatory drugs of high efficacy and a good safety profile have been launched. But the concept of NEDA (No Evidence of Disease Activity) remains the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…However, due to the relatively long period required in getting approval for these drugs (Table 1), already approved monoclonal antibodies, especially those that inhibit IL-6 and TNF, as well as Bevacizumab (Food and Drug Administration, FDA, 2018), Ruxolitinib (FDA, 2019), Baricitinib (FDA, 2018), and Emapalumab (FDA, 2019) may be considered for possible use in the treatment of SARS-CoV-2 infection with associated inflammatory stress or cytokine storm. Even though the effects of these antibodies on neuroinflammation are not known, previous studies have demonstrated a beneficial role of monoclonal antibodies in psychopathological illnesses (Essali et al 2019) and multiple sclerosis (Sirbu and Budisteanu 2020), which are characterized by neuroinflammatory response and blood brain barrier disruption (Welcome 2020a, b).…”
Section: Excessive Inflammatory and Oxidative Stress Due To Immune Dysregulation Is Responsible For Triggering The Cytokine Storm In Sarsmentioning
confidence: 99%
“…However, due to the relatively long period required in getting approval for these drugs (Table 1), already approved monoclonal antibodies, especially those that inhibit IL-6 and TNF, as well as Bevacizumab (Food and Drug Administration, FDA, 2018), Ruxolitinib (FDA, 2019), Baricitinib (FDA, 2018), and Emapalumab (FDA, 2019) may be considered for possible use in the treatment of SARS-CoV-2 infection with associated inflammatory stress or cytokine storm. Even though the effects of these antibodies on neuroinflammation are not known, previous studies have demonstrated a beneficial role of monoclonal antibodies in psychopathological illnesses (Essali et al 2019) and multiple sclerosis (Sirbu and Budisteanu 2020), which are characterized by neuroinflammatory response and blood brain barrier disruption (Welcome 2020a, b).…”
Section: Excessive Inflammatory and Oxidative Stress Due To Immune Dysregulation Is Responsible For Triggering The Cytokine Storm In Sarsmentioning
confidence: 99%
“…While waiting for a vaccine, the completion of which has not materialized for SARS or MERS, so far, a balanced lifestyle, with physical therapy, melotherapy, healthy eating, can lead to a natural increase in immunity (11)(12)(13)(14). Also, new monoclonal antibody therapies that reduce lymphocytes must be weighed well before administration during the pandemic (15).…”
Section: Discussionmentioning
confidence: 99%
“…There is no test predictive of the progression from LTBI to active disease, which is the reason prevention plays an important role. Screening for LTBI is currently recommended before starting daclizumab and alemtuzumab therapy, but not before initiating CD20-acting DMTs (rituximab, ocrelizumab) [26,27]. Additionally, the screening of high-risk groups in the population and the use of infection control measures or chemoprophylaxis are indicated [23].…”
Section: Discussionmentioning
confidence: 99%